Influence of the second phase on relative fracture behavior of friction stir welded 7A52 aluminum alloy. (December 2022) - Liu, Xu; Jia, Ruiling; Cheng, Wenhua; Zhang, Huixia; Tian, Jie; Zhai, Xiwei
Abstract: The mechanical properties of welded joints play a decisive role in service life of the materials, and the second phase particles significantly affect the fracture behavior of the welded joint. In present work, 7A52 aluminum alloy welded joints were prepared by friction stir welding (FSW), the morphologies of different second phases distributed in the joints were observed by SEM, TEM, EBSD and the fracture behavior of the advance side was investigated by in-situ tensile testing. The results show that the fracture is located at the thermo-mechanically affected zone of advance side, where are serious crystal mutation and second phase segregation. Because of poor mechanical properties of the incoherent Mg2 Si phase, the cracking initiated at the interface and showed a characteristic with multi-directional cracking. The incoherent AlFe phase cracked along the direction of shear force, and the separated phase interface provided the main cracking propagation path, which would reduce the energy consumption in the process of cracking propagation and accelerate the propagation speed. The semi-coherent AlMgCu phase with excellent mechanical properties hindered the movement of dislocations and improved the mechanical properties of the joints. Graphical Abstract: ga1